2021
DOI: 10.1155/2021/7488188
|View full text |Cite
|
Sign up to set email alerts
|

m6A-Related lncRNA to Develop Prognostic Signature and Predict the Immune Landscape in Bladder Cancer

Abstract: Abnormal m6A methylation plays a significant role in cancer progression. Increasingly, researchers have focused on developing lncRNA signatures to evaluate the prognosis of cancer patients. The specific function of m6A-related lncRNAs in the prognosis of bladder cancer patients and the immune microenvironment of bladder cancer remains elusive. Herein, we performed a comprehensive analysis of m6A-related lncRNA prognostic values and their association with the immune microenvironment in bladder cancer using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Predictive models based on bioinformatics analysis are widely available in the field of BLCA research, and many of them show high predictive accuracy ( Abudurexiti et al, 2019 ; Li Z. et al, 2021 ; Du et al, 2021 ). However, there are still fewer diagnostic models for predicting the carcinogenesis of BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive models based on bioinformatics analysis are widely available in the field of BLCA research, and many of them show high predictive accuracy ( Abudurexiti et al, 2019 ; Li Z. et al, 2021 ; Du et al, 2021 ). However, there are still fewer diagnostic models for predicting the carcinogenesis of BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…ese processes help to protect tumor cells from clearance, inhibit cell death, and promote proliferation to further aid tumor cell migration and metastasis. Most of the current studies have focused on immunomodulation of tumors [28], focusing on addressing the sustained suppression of adaptive immune responses by TME [29]. Encouragingly, previous studies have demonstrated a strong association between m 6 A methylation and tumor immunotherapy; for example, studies have reported a broad regulatory mechanism of m 6 A on the tumor microenvironment in gastric cancer [25].…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that m6A methylation has significant potential for the development of new human cancer therapies. Additionally, bioinformatics show that m6A participates in BC via multiple biological processes: m6A regulators contribute to malignant progression and impact on prognoses ( Chen et al, 2019d ), m6A contributes to tumor microenvironments ( Zhu et al, 2021b ), and m6A regulates lncRNA in BC carcinogenesis ( Li et al, 2021f ). Moreover, bioinformatics tools can be used to study associations between m6A and BC.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%